Understanding Albanian Culture of Migration: The role of the family in precarious journeys and human trafficking - Brachou, Anta; Lazzarino, Runa; Murphy, Carole; Swan, Eva Karra (Anti-Trafficking Review, 2025)
This article explores families’ roles in precarious journeys and human trafficking from Albania. It demonstrates that familial pressure is a primary driver of migration for many Albanians and sets the family at the centre of the Albanian culture of migration rather than as one of many other factors that can lead to precarious migration and trafficking. The decision to migrate is rarely an individual one; rather, it is often a collective decision where parents, siblings, and extended family members play a crucial role. This is particularly evident in cases where migration is seen as a means to escape poverty or improve social standing, with family members reinforcing the belief that success abroad is the only viable option. The article concludes with recommendations to enhance cultural competence among practitioners and integrate family-oriented considerations in migration policies and interventions, particularly in the United Kingdom.